The role of online medical direction in emergency medical services in India - Wankar, Abhinav Dileep (International Journal of Research in Medical Sciences, 2017)
Medical direction is a system of physician-directed quality assurance that provides professional and public accountability for medical care provided in the prehospital setting. In an Emergency Medical Services (EMS) system, medical direction provides the operational framework and authorization for EMTs and others to provide emergency treatment outside the hospital. While attending and transporting critical patients to a definitive care setting, there is a need for advanced interventions and administration of drugs to the patients, this will alleviate patient suffering and ultimately allow the patient to be delivered to a receiving hospital in an already improved clinical state whenever possible. The Emergency Medical Technician (EMT) in the ambulance is not licensed to administer drugs to the patient on his own. As EMTs are not aware of administering drugs to the patients in critical situation, there is an urgent need to increase the percentage of critical cases with ERCP advice handled by EMT. The current descriptive study has been conducted to identify the hurdles and gaps preventing communication among the EMT and ERCP among a sample of 40 Emergency Medicine staff through a structured questionnaire. The study showed that there are substantial hurdles when the EMT wants to talk to the emergency physician, which can be removed by a few changes like adopting a new method of enhancing skills and training activities, revision of policies and protocols and a few managerial activities.